Contexto institucional para la introducción de la evaluación ambiental estratégica (eae) en Colombia. - Gómez Duque, Jorge (Revista Científica, 2006)
The possibilites of introducing Strategic Environmental Assessment (SEA ) in Colombia (which is applied to level of policies, plans and programs-PPP), it implies to ana;lyze the social-politic context, the processes of management and in general the background in which the public policies are developed, still more considering the variety, specific circumstances, particular forms of formal st4ructuring, different modalities from interdependences, etc. of the existing policies, plans and programs in different scopes.